Evaluacion de poblaciones obtenidas por cultivo in vitro e induccion de mutaciones en platano (Musa spp.) - Jimenez, E.=700 1 Perez Ponce, J.; De Feria, M.; Martin, D.
(En, Es)
ilus., 10 ref.
Keywords: MUSA; CULTIVO IN VITRO; YEMA(PLANTA); MUTACION; CUBA; YEMAS ADVENTICIAS